Energy absorption behavior of tailor-welded tapered tubes under axial impact loading using coupled FEM/SPH method. (July 2016) - Meric, Dursun; Gedikli, Hasan
Abstract: Thin-walled tubes are widely used as energy absorbers. In this study, we evaluated the energy absorbing behavior of empty and aluminum metal foam-filled tubes with different taper angles (0°, 5°, 10°, and 15°) by using the Finite Element Method (FEM)/Smooth Particle Hydrodynamics (SPH) with the Feed forward Neural Network (FNN). Within the scope of the study, tubes composed of AL6061 and AISI1018 materials were designed by using three different weld locations ( L 0 / L =0.25, L 0 / L =0.50, and L 0 / L =0.75). In the welded tubes, the thickness of the lower part (AISI1018) was held constant (1.5 mm), while the thickness of the upper part (AL6061) and the foam density of the filler material were variable (0.5–2.5 mm and 100–800 kg/m 3, respectively). Based on the analysis of the study results, it was determined that empty and foam-filled tubes with a 5° taper angle exhibited the best energy absorbing behavior. In addition, we also determined the optimum upper part thickness and foam density for obtaining the minimum peak force ( Fpeak ) and maximum specific energy absorption (SEA) values. Highlights: Crashworthiness behavior was determined by using coupled FE and SPH method. SEA and peak force increased with increasing upper part thickness and foam density. Peak forces were significantly low for TWTs made from different materials. CFE and ψ decreased with increasing upper part thickness and decreasing welding location. CFE and ψ slightly increased with increasing foam density.